2017
DOI: 10.1080/13696998.2017.1390474
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and economic benefits of professional CGM among people with type 2 diabetes in the United States: analysis of claims and lab data

Abstract: Significant clinical benefits were observed for patients who used professional CGM. Economic benefits were observed for patients who utilized professional CGM more than once within a 1-year period or who used it during a change of diabetes therapy. This suggests that professional CGM may help decrease rising trends in healthcare costs for people with type 2 diabetes, while also improving clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 11 publications
1
33
0
1
Order By: Relevance
“…Professional CGM can be a useful patient teaching tool and can provide important data for pattern identification and insulin dose adjustments. This intervention has been shown to assist patients in reaching their glycemic targets and to improve physical activity and promote other positive behavioral changes (19,20). One study of 52 patients with type 2 diabetes demonstrated that using professional CGM as a part of diabetes education resulted in higher levels of physical activity (P <0.05) and decreases in BMI and A1C compared to patients not using professional CGM (19).…”
Section: Considerations For Selecting a Personal Cgm Systemmentioning
confidence: 99%
“…Professional CGM can be a useful patient teaching tool and can provide important data for pattern identification and insulin dose adjustments. This intervention has been shown to assist patients in reaching their glycemic targets and to improve physical activity and promote other positive behavioral changes (19,20). One study of 52 patients with type 2 diabetes demonstrated that using professional CGM as a part of diabetes education resulted in higher levels of physical activity (P <0.05) and decreases in BMI and A1C compared to patients not using professional CGM (19).…”
Section: Considerations For Selecting a Personal Cgm Systemmentioning
confidence: 99%
“…The use of professional CGM in clinical practice has demonstrated a reduction in the total cost of care and improved glycemic management; however, only for the sub‐groups of patients who utilized a professional CGM more than once within an 1‐year period or those who received an intervention in their diabetes therapy . There was no improvement in glycemic control in those not receiving therapy modification during use.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, the experts suggest: "All patients should receive training in how to interpret and respond to their glucose data […]. Economic benefits were documented in a study from the USA (32). Economic benefits were documented in a study from the USA (32).…”
Section: Glucose Monitoringmentioning
confidence: 99%
“…Patient education and training for CGM should utilize standardized programs with follow-up to improve adherence and facilitate appropriate use of data and diabetes therapies" (28). Economic benefits were documented in a study from the USA (32). An additional field in which CGM seems to be very interesting and helpful is diabetes and pregnancy.…”
Section: Glucose Monitoringmentioning
confidence: 99%